2007
DOI: 10.1038/sj.cgt.7701101
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid 2 receptor induction by IL-12 and its potential as a therapeutic target for the treatment of anaplastic thyroid carcinoma

Abstract: Anaplastic thyroid carcinoma is the most aggressive type of thyroid malignancies. Previously, we demonstrated that tumorigenicity of anaplastic thyroid carcinoma cell line ARO was significantly reduced following interleukin (IL)-12 gene transfer. We suspected that tumor target structure in ARO/IL-12 cells might be changed and such a change may make them more susceptible to be killed through mechanisms apart from natural killer-dependent pathway. To identify genes involved, we examined gene expression profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…IL-12 gene transfer in to anaplastic thyroid carcinoma cell line (ARO) has anti-tumorigenic effect [122]. This effect was observed due to the activation of cannabinoid receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-12 gene transfer in to anaplastic thyroid carcinoma cell line (ARO) has anti-tumorigenic effect [122]. This effect was observed due to the activation of cannabinoid receptor.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was observed due to the activation of cannabinoid receptor. Furthermore they have reported that CB2 agonist JWH-133 and CB1/CB2 agonist WIN-55,212-2 induced apoptosis in ARO and ARO/IL-12 cells [122]. 2-methyl-2'-F-anandamide (Met-F-AEA) also induced apoptosis in thyroid carcinoma cells via activation of p53 and p21 mediated pathway [123].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that activation of cannabinoid receptor 2 (CB2) triggers apoptosis in anaplastic TC cell lines. A considerable regression of thyroid tumors generated by inoculation of ARO/CB2 cells was observed in nude mice following administration of CB2 agonist JWH133 (Shi et al 2008). Data indicating that endocannabinoids are effective against cancer cells with activated BRAF/ERK and/or TrkA signaling suggest its potential utility for the treatment of BRAF-positive PTC and TrkA-positive MTC.…”
Section: Cannabismentioning
confidence: 85%
“…Moreover, CB 2 receptor activation leads to anticancer effects in other tissues. CB 2 receptor overexpression may contribute to the regression of human anaplastic thyroid tumour in nude mice following interleukin-12 gene transfer, [139] suggesting an inhibitory role of CB 2 in thyroid carcinogenesis. In vitro, Met-F-AEA was shown to reduce thyroid tumour growth [79] and to induce apoptosis in thyroid carcinoma cells.…”
Section: Anti-angiogenesis Effectsmentioning
confidence: 99%